Promoting Inclusive Growth in the Caucasus and Central Asia - Vera-Martín, Mercedes (International Monetary Fund. Middle East and Central Asia Department (Series) ;, 2019)
CCA countries achieved gains in inclusiveness over the past 20 years as incomes increased and poverty, inequality, and unemployment declined. Most of the progress occurred before the 2008-09 global financial crisis. Since then, poverty rates have barely moved and, for oil importers, remain elevated.